Selection and Breeding of Dairy Cattle in Western Siberia - V. Kharina , Larisa; A. Korsheva, Inna; V. Markina, Nadezhda; V. Borisenko, Sergey (KnE Life Sciences, 2021)
The main objective of stock breeding is to raise highly productive animals, improve existing ones and create new types and breeds of livestock. The main focus of dairy cattle breeding is on increasing milk yield, fat and protein content in milk; preserving fertility and productive longevity; and developing high adaptive properties of suitability for modern industrial technologies. Selection and breeding of black-and-white and red steppe breeds of cattle is aimed at improving the breeding and productive qualities of the animals. These breeds are traditionally raised in Western Siberia. Breeding to improve the economic and productive features of black-and-white and red steppe breeds of cattle led to the creation of new zonal types, including the Priobsky, Kulunda and Siberian zonal types, which are characterized by relatively high dairy productivity. This study showed that the Siberian type of heifers had the maximum milk yield – 6389 kg, which was 1239 kg and 828 kg more than the Kulunda and Priobsky types, respectively. The same tendency was observed for the third lactation. Animals with a dry period of less than 40 days had lower milk yields than those with a longer period. In terms of the amount of milk and the weight fraction of fat and protein in the milk, the animals exceeded the standard for the parental breed. The duration of pregnancy among the studied animals was within the physiological norm – 276.1-280.8 days. The research results may be of interest to agricultural students and specialists involved in selection issues. Keywords: reproduction, breed, milk productivity